APPLICATION INFORMATION IN ISLAM FIRQAH-FIRQAH USING MICROSOFT VISUAL BASIC 6.0 - Miftachul Fuad; Ire Puspa Wardhani, SKom, MM Ire Puspa Wardhani, SKom, MM (Jurnal Sistem Informasi, 2003)
So far, there are still many Muslims who do not know fully about matters related tothe problem-firqoh firqoh in Islam. Though many of them actually, especiallyMuslims, who wanted to know about how real-firqoh firqoh them. Lack of adequateinformation about these firqoh firqoh-emergence is a major cause of lack ofunderstanding for the most faithful Muslims.This application is made to provide alternative information about firqoh memberiaknusing computerized media so that the necessary information can be found quickly.